Evaluation of a Novel Field-placement Algorithm for Locoregional Breast Cancer Radiotherapy Including the Internal Mammary Chain. Issue 1 (January 2019) - Ranger, A.; Dunlop, A.; Shah, P.; Amin, K.; Henderson, D.; Bartlett, F.R.; Knowles, C.; Brigden, B.; Lacey, C.; Donovan, E.; Harris, E.; Kirby, A.M.
Abstract: Aims: Irradiation of the internal mammary chain (IMC) is increasing following recently published data, but the need for formal delineation of lymph node volumes is slowing implementation in some healthcare settings. A field-placement algorithm for irradiating locoregional lymph nodes including the IMC could reduce the resource impact of introducing irradiation of the IMC. This study describes the development and evaluation of such an algorithm. Materials and methods: An algorithm was developed in which six points representing lymph node clinical target volume borders (based on European Society for Radiotherapy and Oncology consensus nodal contouring guidelines) were placed on computed tomography-defined anatomical landmarks and used to place tangential and nodal fields. Single-centre testing in 20 cases assessed the success of the algorithm in covering planning target volumes (PTVs) and adequately sparing organs at risk. Plans derived using the points algorithm were also compared with plans generated following formal delineation of nodal PTVs, using the Wilcoxon signed rank test. Timing data for point placement were collected. Multicentre testing using the same methods was then carried out to establish whether the technique was transferable to other centres. Results: Single-centre testing showed that 95% of cases met the nodal PTV coverage dose constraints (binomial probability confidence interval 75.1–99.9%) with no statistically significant reduction in mean heart dose or ipsilateral lung V17Gy associated with formal nodal delineation. In multicentre testing, 69% of cases met nodal PTV dose constraints and there was a statistically significant difference in IMC PTV coverage using the points algorithm when compared with formally delineated nodal volumes ( P < 0.01). However, there was no difference in axillary level 1–4 PTV coverage ( P = 0.11) with all cases meeting target volume constraints. Conclusions: The optimal strategy for breast and locoregional lymph node radiotherapy is target volume delineation. However, use of this novel points-based field-placement algorithm results in dosimetrically acceptable plans without the need for formal lymph node contouring in a single-centre setting and for the breast and level 1–4 axilla in a multicentre setting. Further quality assurance measures are needed to enable implementation of the algorithm for irradiation of the IMC in a multicentre setting. Highlights: Novel algorithm allows field-based locoregional breast RT planning (including IMC) without the need for nodal delineation. Target volume coverage/organ at risk dose constraints can be met by placing six points on the peripheries of lymph node CTVs. Potential resource saving option for IMC radiotherapy.